2019
DOI: 10.1093/brain/awz325
|View full text |Cite
|
Sign up to set email alerts
|

Hitting the brakes: pathological subthalamic nucleus activity in Parkinson’s disease gait freezing

Abstract: The neurobiology of gait freezing in Parkinson’s disease is poorly understood and therapies are largely ineffective. Using a virtual reality task to elicit freezing intra-operatively during implantation of DBS electrodes, Georgiades et al. identify pathological subthalamic nucleus activity associated with freezing onset and discernible from that of volitional stopping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…The definition of FOG in this VR paradigm therefore remains arbitrary 21,27 . Still, the degree of FOG tested during the VR task correlated with FOG during actual gait 58 , and a study using electromyography of the legs showed that VR-defined FOG events in eight people with PD were characterized by an increased freezing-ratio 82 resembling the severe trembling of the legs observed during FOG in the clinic 83 . Future studies adopting electromyography or position data of the feet in large samples are needed to fully validate this paradigm.…”
Section: [H2] Brain Imaging Resultsmentioning
confidence: 98%
“…The definition of FOG in this VR paradigm therefore remains arbitrary 21,27 . Still, the degree of FOG tested during the VR task correlated with FOG during actual gait 58 , and a study using electromyography of the legs showed that VR-defined FOG events in eight people with PD were characterized by an increased freezing-ratio 82 resembling the severe trembling of the legs observed during FOG in the clinic 83 . Future studies adopting electromyography or position data of the feet in large samples are needed to fully validate this paradigm.…”
Section: [H2] Brain Imaging Resultsmentioning
confidence: 98%
“…Indeed, dynamic balance activities including walking indicate that PD who freeze exhibit more activity of the frontal cortex than those who do not freeze [25]. Further, these increased demands on the cortico-basal ganglia system may place the individual closer to a freezing event, which could be triggered by a cognitive, affective, or motor conflict [26], underpinned by a de-coupling of the cortico-thalamic system [27].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the limited evidence, an investigation into neural markers of conversion is warranted for additional predictive purposes and to help explain the elusive mechanisms leading to the onset of FOG 19 . While freezing episodes likely signify transient dysfunctional information processing across the cortico-basal ganglia-thalamo-cortical parallel circuits [20][21][22] , these transient events are challenging to elicit and interpret, and therefore have poor applicability as predictive markers. Compensatory or maladaptive structural alterations of the nodes within these circuits, however, are more persistent and therefore easier to capture as possible predictive markers for FOG in PD.…”
Section: Introductionmentioning
confidence: 99%